Ecotourism what is it - Been, Peter; Classrom Video ([New Jersey] : Classroom Video : Insight Media [distributor], 1998)
Examines the debate over what constitutes ecotourism, examining the question in detail and focuses on three ecotourism activities
Title from container
Executive producer, John Davis ; editing, Phil Sheppard ; sound, Dominique Fusy, Philip McGuire, Konrad Skirlis ; consultant, Susan Bliss
Keywords: Ecotourism; Tourism